Adult Education Program Implementers’ Understanding and Usage of Strategy Policy Documents in Addis Abab City Administration, Ethiopia - Million Tadesse (SAGE Open, 2024)
This study was targeted to assess adult education program implementers’ understanding towards adult education policy documents and usage of the documents in Addis Ababa City Administration. In order to guide the study qualitative method was applied. Accordingly, qualitative data was gathered using interview and document analysis. Qualitative data like views of respondents and result gained from document analysis were discussed by narrating the evidences/responses in words. As the findings of this study reveals, majority of adult education program implementers lack understanding about the policy documents of adult education sector; there is no established and sustainable awareness creation system and capacity building program for newly employed and other personnel; non-existence an established structure to lead adult education program according to the designed strategy documents are some of the results of the research. In order to overcome the challenges mentioned above adult education implementing organizations have to launch continuous professional development (CPD) program for implementers of adult education program. Consequently, implementers of the program can get first-hand information on the policy documents on one hand and they can also upgrade their profession on the other hand.